Social and Cultural Factors as Determinants of Divorce: A Study at the Banyuwangi Religious Court - Raisya Salwa Kasyara; Muhammad Nurul Fahmi (STAI Serdang Lubuk Pakam, 2026)
This study examines social and cultural factors as determinants of divorce in the Banyuwangi Religious Court during 2020–2025. Divorce cases remained consistently high, ranging from 5,570 to 6,091 annually, with wife-initiated divorces rising from 68.8% in 2020 to 75.25% in 2025. Using a qualitative descriptive-analytical approach, data were collected through interviews with the Chief Judge and analysis of ten divorce rulings issued between 2021 and 2025. Four key socio-cultural determinants were identified: the influence of social media in shaping unrealistic marital expectations; shifting gender roles linked to women’s growing economic independence; cultural acculturation through Banyuwangi’s tourism sector, which heightened risks of infidelity; and economic vulnerability exacerbated by inadequate pre-marital preparation, addictive behaviors, and the prolonged impact of the Covid-19 pandemic. The study also reveals an epistemological gap between complex social realities and administrative legal classifications, as diverse marital conflicts are often grouped under the broad category of “continuous disputes.” These findings highlight the need to strengthen pre-marital education, culturally responsive family mediation, and more comprehensive divorce recording systems to support effective family resilience policies.